2008
DOI: 10.1055/s-2007-1000428
|View full text |Cite
|
Sign up to set email alerts
|

Ist eine Pleuritis sonographisch darstellbar?

Abstract: We conclude that chest sonography is a sensitive and cost effective imaging method for the diagnosis of pleuritis. Aspiration of pleural fluid for further diagnostic or therapeutic procedures can be safely performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…16 Similarly, pleural line abnormalities and small consolidations have varied and inconsistent definitions. Early work described a normal pleural line measuring up to 2 mm, 17,18 with abnormal pleura described as "thickened" with "hypoechoic broadening" 17 and measuring either more than 2 mm 18 or 3 mm [19][20][21] -all based on a linear array probe; however, as the pleural "thickness" observed in lung ultrasound is an artifact, its absolute width has no pathological correlate. 22 An international expert panel simply refers to an abnormal pleural line as "irregular" and "fragmented" with no size threshold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Similarly, pleural line abnormalities and small consolidations have varied and inconsistent definitions. Early work described a normal pleural line measuring up to 2 mm, 17,18 with abnormal pleura described as "thickened" with "hypoechoic broadening" 17 and measuring either more than 2 mm 18 or 3 mm [19][20][21] -all based on a linear array probe; however, as the pleural "thickness" observed in lung ultrasound is an artifact, its absolute width has no pathological correlate. 22 An international expert panel simply refers to an abnormal pleural line as "irregular" and "fragmented" with no size threshold.…”
mentioning
confidence: 99%
“…3 Rarely has a size criterion been assigned to consolidation, with both ≥15 mm 23 or 2-20 mm previously described. 17 When B-line interpretation has been assessed, the interobserver agreement on its presence has been moderate. For example, Haaksma et al demonstrated that the agreement on <3 or ≥3 B-lines is transducer and rater dependent.…”
mentioning
confidence: 99%
“…Ultrasound demonstrates a fragmented pleural reflex with small subpleural consolidations and multiple B-lines (fig. 11) [23]. …”
Section: Sonography and Sonomorphology Of Important Thoracic Emergenciesmentioning
confidence: 99%
“…Ultrasonography is the most sensitive method for the verification of septa. A preceding sonographic examination may avoid [19]. Die pleurale entzündliche Hyperämie kann im kontrastverstärkten Ultraschall nachgewiesen werden, dies ist in der Routinediagnostik allerdings verzichtbar [20].…”
Section: Complex Pleural Effusionunclassified
“…In 90 % of patients with pleuritis a thickening and roughening of the pleura can be seen on the usually smooth pleural membrane during sonographic examination of the area of pain. In two thirds of cases small subpleural infiltration can be detected on the side of the lung, as can localized or basal pleural effusions [19]. Inflammatory pleural hyperemia is proven to exist with contrastenhanced ultrasound, but this finding is expendable in routine diagnostics [20].…”
Section: Pleurisymentioning
confidence: 99%